Racial profiling: using propensity score matching to examine focal concerns theory - Vito, Anthony Gennaro (Routledge focus, 2017)
1. Introduction -- 2. Focal concerns theory, propensity score matching, and racial profiling -- 3. Traffic stop data from the Louisville Police Department -- 4. Propensity score matching results -- 5. Policy implications for racial profiling.